Cittadini e no Forme e funzioni dell'inclusione e dell'esclusione - Mindus, Patricia (Studi e saggi, 2014)
The theme of "citizenship" has become very topical once again. Who should be considered a citizen? What does it mean to be a citizen? What are the mechanisms regulating inclusion and exclusion from citizenship? How can these mechanisms be justified and criticized? Using a multidisciplinary approach, the volume presents some studies on citizenship, moving across political science, case-law and social sciences. The aim of the volume is to reconstruct the debate, with references to empirical cases, and, on the basis of conceptual analysis, to enable a discussion on the main models of citizenship and on the different forms they have taken on in history. The suggested functional theory provides a tool to establish whether the attribution of the said status is justified or not.